Preparation and Characterization of Magnetic Material/Chitosan Composite Modified with Glycidyl-Trimethylammonium Chloride - Feri Mukhayani; Eko Sri Kunarti; Yuichi Kamiya; Nuryono Nuryono (Universitas Gadjah Mada, 2024)
Glycidyl-trimethylammonium chloride (GTMAC) containing quaternary ammonium (QA) groups is commonly used as a base catalyst for any organic reaction. This research prepared a novel composite of GTMAC attached to chitosan-coated magnetic material (MM/Chi/GTMAC) using a precipitation method. The effect of chitosan and GTMAC contents on MM/chi/GTMAC properties was studied, where the chitosan content varied from 0, 0.3, 0.5, 1.0, and 3.0 mol, and GTMAC varied from 0, 0.3, 0.8, 1.0, 1.5, and 3 mL with the constant mass of MM (0.4640 g). The physicochemical and morphological properties were characterized with FTIR, SEM-EDX, XRD, TGA, UV-vis, AAS, and zeta-sizer, and the magnetic strength was simply tested with an external magnet. The result showed that a mixture containing chitosan and GTMAC of 0.358 g and 1.5 mL was an optimum composition, in which MM/chi(0.5)/GTMAC(1.5) has high thermal stability, low chitosan and Fe solubility, and optimum content of QA (0.284 mol/g) without loss of magnetic strength. The higher the amount of chitosan, the lower the magnetic properties, and the higher the GTMAC did not increase the QA content. Therefore, the composite produced has the potential to be a novel heterogeneous base catalyst that is quickly recovered from any organic reaction media.